Incidence of respiratory infections and its correlation with smoke exposure among infants from an urban field practice area in Tamil Nadu - Saravana Kumar P; Subhalakshmi R; Rajasekeran C; Elizabeth Varakumari Janakiraman (Asian Journal of Medical Sciences, 2023)
Background: Children’s acute lower respiratory infections are most prevalent among new-born. Clinical evaluation and symptoms help to establish the connection between smoke exposure and acute respiratory tract infection (ARTI). Furthermore, there is proof that exposing children to coal smoke considerably increases their risk of developing ARTI. Aims and Objectives: This study was designed to estimate the incidence of respiratory tract infection (RTI) among selected cohort of infants in urban field practice area of Tamil Nadu and to correlate the incidence of RTIs with smoke practices. Materials and Methods: In Tamil Nadu’s urban field practice area, a cohort study of infants was done. A house-to-house survey was conducted and information was gathered among 150 newborns who were tracked after being selected as a period sample based on inclusion criteria at a 15* visit. Numerous data on ARI episodes, housing circumstances, and smoke exposure were gathered and correlated. Software such as Epi info and SPSS version 22 were used to analye data. Results: The incidence of TI was calculated to be 1.7 episodes per 100 person days and 4.7 on average among the 150 newborns chosen. Nearly 48% of people lived in huts, 84% had indoor kitchens, and 75% cooked with gas. Infants who appeared to regularly be exposed to passive smoking have a little increase in the incidence of mean RTI bouts. Conclusion: The additional hospital admissions, which are entirely preventable, place a heavy load on the public health system. It is evident that new initiatives are required to stop infants from being exposed to passive smoke during and after pregnancy. Improving international Electrotechnical commission activities play an active role is reducing incidence of RTIs among infants. Intensified educational interventions on ill effects of indoor and outdoor smoke, passive smoking helps in addressing the issue.